The Effect Of Motivation And Job Satisfaction On Intervening Work Performance In The Personnel Agency Langkat Regency Area - Doa Jafar; Emi Wakhyuni (International Journal of Management, Economic and Accounting, 2025)
Human resource management is part of organizational management that focuses on human resource elements. The task of MSDM is to manage the human element well so that a workforce that is satisfied with its work is obtained. In an organization, human beings are one of the most important elements in an organization. Without the role of human beings, even though the necessary factors are available, the organization will not run. Job Satisfaction had a positive and significant effect on Organizational Commitment with a value of 0.598 and a significant 0.000. Job Satisfaction had a positive and significant effect on Job Achievement with a value of 0.517 and a significant 0.000. Organizational Commitment had a positive and insignificant effect on Work Achievement with a value of 0.176 and a significant 0.057. Motivation had a positive and significant effect on Organizational Commitment with a value of 0.278 and a significant 0.035. Motivation had a positive and significant effect on Work Achievement with a value of 0.274 and a significant 0.020. Job Satisfaction had a positive and insignificant effect on Work Performance through Organizational Commitment with a value of 0.105 and a significant 0.061. Motivation has a positive and insignificant effect on Work Performance through Organizational Commitment with a value of 0.049 and a significant 0.165,